CSF-flow prior and after spinal tap test in patients with idiopathic normal pressure hydrocephalus—an exploratory study using real-time phase-contrast MRI - Dierksen, Fiona; Heide, Marielle; Hofer, Sabine; Bernsdorff, Felix; Dechent, Peter; von der Brelie, Christian; Rohde, Veit; Liman, Jan; Bähr, Mathias; Maier, Ilko L. (Frontiers in Neuroimaging, 2025)
BackgroundNeuroimaging plays a key role in the diagnostic workup of patients with idiopathic normal pressure hydrocephalus (iNPH). A flow void in the aqueduct - indicating increased cerebrospinal fluid (CSF) velocity - is a common, but unspecific finding. Aim of this study was to investigate CSF-flow characteristics in iNPH patients before and after spinal tap test (STT) using novel, real-time phase-contrast magnetic resonance imaging (RT-PC MRI).MethodsWe included consecutive patients with clinical signs of iNPH being electively admitted for diagnostic workup, including neurological examination, conventional MRI and STT. RT-PC MRI and clinical examination were performed before and within 24 h after STT. CSF-flow volumes were determined at five regions in the inner and outer CSF spaces.ResultsFifteen patients with suspected iNPH and five age-matched healthy controls (HC) were included. Baseline RT-PC MRI revealed elevated CSF-flow volumes in the inner ventricular system of iNPH patients compared to healthy controls, being detectable predominantly in the third ventricle (iNPH vs. HC: 15.93 ± 7.01 mL vs. 6.58 ± 2.99 mL, p = 0.020). There was a positive correlation between the Evans Index and CSF-flow in the third ventricle (r = 0.586, p = 0.017), cerebral aqueduct (r = 0.639, p = 0.006) and the fourth ventricle (r = 0.649, p = 0.007). There was no statistically significant change of CSF-flow volumes before and after STT in the iNPH-group.ConclusionRT-PC MRI provides a promising, non-invasive approach for evaluating CSF-flow in iNPH. Baseline CSF-flow volumes were elevated in the inner ventricular system, particularly in the third ventricle, and correlated with ventricular enlargement, suggesting that increased CSF-flow may reflect disease progression rather than therapeutic response. However, in contrast to clinical tests, the lack of change of CSF-flow after STT limits its utility for patient selection for ventriculo-peritoneal-shunt implantation.